Discounting of Deferred Taxes: Theoretical Aspects - A. A. Aksent'ev (Учёт. Анализ. Аудит)
The objective of the study is to justify the prohibition of discounting deferred taxes by harmonising their essence with the concept of fair value. The work is theoretical in nature, standard scientific methods have been used, including the collection of theoretical information, formalisation, as well as analysis, synthesis, observation, and comparison. This article summarizes the results of research in the field of deferred tax discounting over the past 60 years and attempts to reconcile the essence of it with the concepts of fair value. The issues of deferred tax discounting have long been the subject of scientific research and still remain unresolved. In the second half of the twentieth century, the key problem was the choice of an acceptable discount rate against the background of lack of understanding of the essence of deferred taxes. Subsequently, the vector of research has changed towards determining the economic value of deferred taxes without reference to the theory of deferred taxation. The author proved that under the concept of fair value, deferred tax liabilities (DTL) do not need to be discounted because the assessment takes into account the minimum economic benefits generated by the asset as of the reporting date and under prevailing market conditions. It is shown that the balance sheet reflects the theoretical relationship between deferred tax liabilities and current income tax liabilities. The conclusion is made about the modifiability of deferred tax liabilities into current liabilities in terms of static accounting ideology while observing the going concern principle. The problems of applying valuation at fair value measurement that does not take into account the current tax position of the organization; as well as the place of deferred taxes in the capital accounting equation are raised. The results of the research have theoretical significance and can be used within the framework of improvement of the accounting legislation.